Animal models in neonatal resuscitation research: What can they teach us?. Issue 5 (October 2018) - Hooper, Stuart B.; te Pas, Arjan B.; Polglase, Graeme R.; Wyckoff, Myra
Abstract: Animal models have made and continue to make important contributions to neonatal medicine. For example, studies in fetal sheep have taught us much about the physiology of the fetal-to-neonatal transition. However, whereas animal models allow multiple factors to be investigated in a logical and systematic manner, no animal model is perfect for humans and so we need to understand the fundamental differences in physiology between the species in question and humans. Although most physiological systems are well conserved between species, some small differences exist and so wherever possible the knowledge generated from preclinical studies in animals should be tested in clinical trials. However, with the rise of evidence-based medicine the distinction between scientific knowledge generation and evidence gathering has been confused and the two have been lumped together. This misunderstands the contribution that scientific knowledge can provide. Science should be used to guide the gathering of evidence by informing the design of clinical trials, thereby increasing their likelihood of success. While scientific knowledge is not evidence, in the absence of evidence it is likely to be the best option for guiding clinical practice.